External validation of the parental attitude about childhood vaccination scale - Ghazy, Ramy Mohamed; Elkhadry, Sally Waheed; Abdel-Rahman, Suzan; Taha, Sarah Hamed N.; Youssef, Naglaa; Elshabrawy, Abdelhamid; Ibrahim, Sarah Assem; Al Awaidy, Salah; Al-Ahdal, Tareq; Padhi, Bijaya Kumar; Fadl, Noha (Frontiers in Public Health, 2023)
Introduction: Internal validation techniques alone do not guarantee the value of a model. This study aims to investigate the external validity of the Parental Attitude toward Childhood Vaccination (PACV) scale for assessing parents' attitudes toward seasonal influenza vaccination. Methods: Using a snowball sampling approach, an anonymous online questionnaire was distributed in two languages (English and Arabic) across seven countries. To assess the internal validity of the model, the machine learning technique of "resampling methods" was used to repeatedly select various samples collected from Egypt and refit the model for each sample. The binary logistic regression model was used to identify the main determinants of parental intention to vaccinate their children against seasonal influenza. We adopted the original model developed and used its predictors to determine parents' intentions to vaccinate their children in Libya, Lebanon, Syria, Iraq, Palestine, and Sudan. The area under the curve (AUC) indicated the model's ability to distinguish events from non-events. We visually compared the observed and predicted probabilities of parents' intentions to vaccinate their children using a calibration plot. Results: A total of 430 parents were recruited from Egypt to internally validate the model, and responses from 2095 parents in six other countries were used to externally validate the model. Multivariate regression analysis showed that the PACV score, child age (adolescence), and Coronavirus disease 2019 (COVID-19) vaccination in children were significantly associated with the intention to receive the vaccination. The AUC of the developed model was 0.845. Most of the predicted points were close to the diagonal line, demonstrating better calibration (the prediction error was 16.82%). The sensitivity and specificity of the externally validated model were 89.64% and 37.89%, respectively (AUC=0.769). Conclusions: The PACV showed similar calibration and discrimination across the six countries. It is transportable and can be used to assess attitudes towards influenza vaccination among parents in different countries using either the Arabic or English version of the scale.